PENGARUH DESIGN INTERIOR DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PESENKOPI DI KOTA MALANG (STUDI MAHASISWA JURUSAN ADMINISTRASI NIAGA POLITEKNIK NEGERI MALANG) - Rahmatu Rabiah; Mohammad Maskan (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
The purpose of this research is to analyze he effect of interior design and the location of purchasing decisions at Pesenkopi in Malang City. This research is a quantitative study with variable interior design and location. This study used a questionnaire data collection technique using purposive sampling technique to 100 respondents of Malang Pesenkopi consumers. Then, the data were analyzed using multiple linear regression analysis, t test and F test. The results of the research show that Interior Design and Location has a percentage coefficient of determination or influence of 51.2% and Location is the dominant influence on purchasing decisions with a coefficient of 0.508 compared to Interior Design with a coefficient of 0.298.